Starting to smoke: a qualitative study of the experiences of Australian indigenous youth - Johnston Vanessa; Westphal Darren W; Earnshaw Cyan; Thomas David P (BMC, 2012)
Abstract Background Adult smoking has its roots in adolescence. If individuals do not initiate smoking during this period it is unlikely they ever will. In high income countries, smoking rates among Indigenous youth are disproportionately high. However, despite a wealth of literature in other populations, there is less evidence on the determinants of smoking initiation among Indigenous youth. The aim of this study was to explore the determinants of smoking among Australian Indigenous young people with a particular emphasis on the social and cultural processes that underlie tobacco use patterns among this group. Methods This project was undertaken in northern Australia. We undertook group interviews with 65 participants and individual in-depth interviews with 11 youth aged 13-20 years led by trained youth 'peer researchers.' We also used visual methods (photo-elicitation) with individual interviewees to investigate the social context in which young people do or do not smoke. Included in the sample were a smaller number of non-Indigenous youth to explore any significant differences between ethnic groups in determinants of early smoking experiences. The theory of triadic influence, an ecological model of health behaviour, was used as an organising theory for analysis. Results Family and peer influences play a central role in smoking uptake among Indigenous youth. Social influences to smoke are similar between Indigenous and non-Indigenous youth but are more pervasive (especially in the family domain) among Indigenous youth. While Indigenous youth report high levels of exposure to smoking role models and smoking socialisation practices among their family and social networks, this study provides some indication of a progressive denormalisation of smoking among some Indigenous youth. Conclusions Future initiatives aimed at preventing smoking uptake in this population need to focus on changing social normative beliefs around smoking, both at a population level and within young peoples' immediate social environment. Such interventions could be effectively delivered in both the school and family environments. Specifically, health practitioners in contact with Indigenous families should be promoting smoke free homes and other anti-smoking socialisation behaviours.